Adenosine signaling in glia modulates metabolic state-dependent behavior in Drosophila - Jean-François De Backer; Thomas Karges; Julia Papst; Zeynep Nigar Pınar; Cristina Coman; Robert Ahrends; Yanjun Xu; Cristina García-Cáceres; Ilona C. Grunwald Kadow (Cell Reports)
Summary: An animal’s metabolic state strongly influences its behavior. Hungry animals prioritize food-seeking and feeding behaviors, while sated animals suppress these behaviors to engage in other activities. Additionally, neuronal activity and synaptic transmission are among the most energy-expensive processes. However, neurons do not uptake nutrients from the circulation. Instead, glia fulfill this highly evolutionarily conserved function in addition to modulating neuronal activity and behavior. However, how different glia subtypes sense metabolic state and modulate behavior is incompletely understood. Here, we unravel two types of glia-mediated modulation of metabolic-state-dependent behavior. In food-deprived flies, astrocyte-like and perineurial glia promote foraging and feeding, respectively, while cortex glia suppress these behaviors. We further show that adenosine and adenosine receptors modulate intracellular calcium levels in these glia subtypes, which ultimately controls behavior. This study reveals a mechanism of how different glia subtypes sense an animal’s metabolic state and modulate its behavior accordingly.